Utilizing Maize Cob Media as a Replacement for Nutrient Agar Media in the Growth of Escherichia coli and Staphylococcus aureus Bacteria - Aldiana Astuti; Ni Made Susilawati; Agnes Peni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Bacteria are microorganisms that require adequate media and nutrients to grow and develop. The media commonly used to grow bacteria is Nutrient agar media, but the price of Nutrient agar media is quite expensive. Corn cobs are lignocellulosic wastes that contain nutrients that can meet the nutritional requirements of bacterial growth media. This study aims to investigate the viability of corn cobs as a cost-effective alternative to Nutrient agar media. Specifically, we explore the variance in bacterial colony growth when utilizing corn cobs as a growth medium for Escherichia coli and Staphylococcus aureus bacteria. Employing a true experimental design with a posttest-only control structure, we analyze the treatment's effects using the One Way ANOVA test and Independent Sample T-test. These statistical methods enable us to discern differences between groups utilizing corncob media with and without added sugar.Our findings reveal noteworthy insights into bacterial colony growth. For Escherichia coli, the average number of colonies on corncob media with sugar was 222 CFU/ml, on corncob media without sugar, it was 164 CFU/ml, and on Nutrient agar media, it reached 361 CFU/ml. In the case of Staphylococcus aureus, colonies on corncob media with sugar averaged 871 CFU/ml, on corncob media without sugar, they averaged 657 CFU/ml, and on Nutrient agar media, they reached 942 CFU/ml.Statistical analysis using the One Way ANOVA test for both Escherichia coli and Staphylococcus aureus demonstrated p-values <0.05, signifying significant differences in their growth on corncob media with sugar, corncob media without sugar, and Nutrient agar media. Furthermore, the Independent Sample T-test results for both bacterial strains yielded p-values <0.05, indicating dissimilar growth patterns on corncob media with sugar compared to corncob media without sugar.In conclusion, our study underscores significant disparities in the growth of Escherichia coli and Staphylococcus aureus bacteria among Nutrient agar media, corncob media with sugar, and corncob media without sugar. Notably, we observed a marked increase in bacterial colony counts on corncob media with sugar and corncob media without sugar.